Relationship Between Maternal Behavior During Pregnancy, Birth Outcome, and Early Childhood Development: An Exploratory Study - Kai Li; Dale J. Poirier (Center for Economic Studies and ifo Institute (CESifo), 2003)
This study examines the relationship between maternal behavior during pregnancy, birth outcomes, and early childhood development. Specifically, in the context of four measures of maternal behavior during pregnancy (maternal smoking, drinking, prenatal care, and maternal weight gain), three measures of birth outcome (gestational age, birth length, and birth weight), and 32 exogenous covariates observed during pregnancy, we investigate the importance of maternal choices during pregnancy and birth outcomes in forecasting child health (as indicated by height and weight), child behavioral problems, and a child math/reading test score at age five or six. Strikingly, birth outcomes have virtually no structural/causal effects on early childhood developmental outcomes, and only maternal smoking and drinking during pregnancy have some effects on child height. Not surprisingly, family child-rearing environment has sizeable negative and positive effects on behavioral problems index and math/reading test score, respectively, and a mildly surprising negative effect on child height.
Keywords: 330; endogeneity; birth weight; NLSY; prediction; simultaneous equations